MULTI DRUG RESISTANT TUBERCULOSIS IN PREGNANCY - muharam, maulana; Firina, Dewi Wahyu; Mizarti, Dessy (Fakultas Kedokteran Universitas Andalas, 2022)
Tuberculosis can develop to multi drug resistant tuberculosis, this will be a serious health problem, not only in Indonesia, also in the world. This disease complexity, length of treatment, adverse effect of drug, make it management become challenging. Pregnancy with physiological changes in it made pregnant woman susceptible to infection, include tuberculosis infection. Data about MDR TB in pregnancy were not much, because TB screening in pregnancy were not often done, also pregnancy it self almost exclude from any trial. Because of MDR TB regiment adverse effect, much of clinician suggest woman in MDR TB treatment to not get pregnant while on it. Management MDR TB on pregnancy use individual regiment, by keep secure and safety aspect of patient, also her fetus.